Immune Regulation of Adult Neurogenic Niches in Health and Disease - Chintamen, Sana; Imessadouene, Fatima; Kernie, Steven G. (Frontiers in Cellular Neuroscience, 2021)
Microglia regulate neuronal development during embryogenesis, postnatal development, and in specialized microenvironments of the adult brain. Recent evidence demonstrates that in adulthood, microglia secrete factors which modulate adult hippocampal neurogenesis by inhibiting cell proliferation and survival both in vitro and in vivo, maintaining a balance between cell division and cell death in neurogenic niches. These resident immune cells also shape the nervous system by actively pruning synapses during critical periods of learning and engulfing excess neurons. In neurodegenerative diseases, aberrant microglial activity can impede the proper formation and prevent the development of appropriate functional properties of adult born granule cells. Ablating microglia has been presented as a promising therapeutic approach to alleviate the brain of maladaptive immune response. Here, we review key mechanisms through which the immune system actively shapes neurogenic niches throughout the lifespan of the mammalian brain in both health and disease. We discuss how interactions between immune cells and developing neurons may be leveraged for pharmacological intervention and as a means to preserve adult neurogenesis.